Factors associated with preeclampsia among pregnant women attending health clinics in Jasin District, Malacca, Malaysia Year 1999-2000 - Muhamad, Yusmah
This cross-sectional study estimated the prevalence of preeclampsia and the associations between preeclampsia and age, race and body mass index among pregnant women attending government health clinics in Jasi District, Malacca, Malaysia. This study utilized data from the antenatal cards of the pregnant women registered for antenatal care in 1999 to 2000. The prevalence of preeclampsia in the study population was 4.4%. The prevalence was highest in the youngest age group (17.7%) followed by the oldest age group (7.54%) and then middle age group (2.79%). Among the three races, the prevalence was highest in the Indian race (6.27%) followed by the Malay race (4.39%) and the Chinese race (3.01%). The prevalence was also higher among overweight or obese women (6.96%) than in women with normal weight (3.49). The result multivariate analysis showed that there was a significant association between preeclampsia and age. Parity, body mass index and history of preeclampsia interactd with the association between preeclampsia and age. The ORs were adjusted for the actual confounder namely preexisting medical condition. There was also a significant association between preeclampsia and body mass index. Age modified the association between preeclampsia and body mass index. The Ors were adjusted for the actual confounders namely parity and history of preeclampsia. The effect of high body mass index on preeclampsia was strongest in the youngest group (ORadj = 6394; 95%CI: 2.82-17.07), followed by the middle aged group (ORadj = 1.62; 95%CI: 1.03-2.60) and the oldest group (ORadj = 1.46; 95%CI: 0.77-2.78). However, race was not found to be associated with preeclampsia. Mothers with the risk factors identified should be monitored more closely and should be assessed by obstetricians periodically. Based on the results of this study, it is recommended that a health education program specially tailored for obese young women should be initiated.
Thesis (MS Epidemiology, Public Health)--University of the Philippines, Manila
Keywords: Preeclampsia